Bilateral anterior uveitis secondary to erlotinib - Lim, Lik Thai; Blum, Robert Alexander; Chee, Peng Cheng; Abdul, Hanifudin (Springer-Verlag, 2010)
We would like to report the first case of bilateral severe anterior uveitis secondary to erlotinib. Erlotinib is an epidermal growth factor receptor (EGFR) inhibitor which can contain certain cancer cells [1]. It is licensed for use in patients with non-small-cell lung carcinoma (NSCLC) in the UK as a secondary treatment for those patients who fail to respond to standard chemotherapy.